Childhood nephrotic syndrome in Africa: Epidemiology, treatment trends, and outcomes (2022)
Nephrotic syndrome is a common childhood glomerular disease that is associated with massive proteinuria and edema. Children with nephrotic syndrome are at risk of chronic kidney disease, disease-related complications, and treatment-related complications. Patients with frequently relapsing disease or steroid toxicity may require newer immunosuppressive medications. However, access to these medications is limited in many African countries owing to prohibitive cost, the need for frequent therapeutic drug monitoring, and a lack of appropriate facilities. This narrative review examines the epidemiology of childhood nephrotic syndrome in Africa, including trends in treatment and patient outcomes. In most of North Africa, as well as among White and Indian populations in South Africa, the epidemiology and treatment of childhood nephrotic syndrome closely resembles that of European and North American populations. Historically, secondary causes of nephrotic syndrome (eg, quartan malaria nephropathy and hepatitis B−associated nephropathy) were predominant among Blacks in Africa. Over time, the proportion of secondary cases has decreased, along with rates of steroid resistance. However, focal segmental glomerulosclerosis increasingly has been reported among patients with steroid resistance. There is a need for consensus guidelines for the management of childhood nephrotic syndrome in Africa. Furthermore, establishing an African nephrotic syndrome registry could facilitate monitoring of disease and treatment trends, and provide opportunities for advocacy and research to improve patient outcomes.